1990
DOI: 10.1038/hdy.1990.74
|View full text |Cite
|
Sign up to set email alerts
|

Adult size and mate choice in seaweed flies (Coelopa frigida)

Abstract: The willingness to mate of pairs of seaweed flies (Coelopa frigida) was measured using a stock known not to exhibit female mate choice with respect to a chromosomal inversion. Mating success was strongly correlated with the size of the female, but not at all with male size. Mating success was not associated with the size difference between the male and female in a pair, except when the male was considerably larger than the female, when mating success was reduced. The components of mating behaviour were quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…excluding sexual selection) is that males of intermediate size are the fittest (see for example Day et al, 1983). In contrast, sexual selection in the form of both female mate choice and male mate choice (Pitafi, 1991; unpublished observations) must operate directionally favouring large size. We therefore have, in seaweed flies, the situation predicted by Fisher (1930) in which natural and sexual selection act in opposition.…”
Section: Discussionmentioning
confidence: 99%
“…excluding sexual selection) is that males of intermediate size are the fittest (see for example Day et al, 1983). In contrast, sexual selection in the form of both female mate choice and male mate choice (Pitafi, 1991; unpublished observations) must operate directionally favouring large size. We therefore have, in seaweed flies, the situation predicted by Fisher (1930) in which natural and sexual selection act in opposition.…”
Section: Discussionmentioning
confidence: 99%
“…No evidence exists of any direct advantage to mating with large males, but this possibility certainly cannot be excluded. There is, however, evidence of a cost to mating in that mating appears to reduce longevity (Pitafi, 1991;Gilburn & Day, in preparation). A similar relationship has been found in Drosophila melanogaster (Partridge et at., 1987;Fowler & Partridge, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore paid only by RR females and results in a proportion, m, of females failing to produce progeny. As in other insect species (Partridge et al, 1987;Fowler & Partridge, 1989;Rowe et a!., 1994), mating in seaweed flies carries a cost; Pitafi (1991) found that females allowed unlimited matings died younger than did virgin females. Furthermore, a positive correlation exists between the frequency of rejection and female longevity (Gilburn & Day, in preparation).…”
Section: The Modelmentioning
confidence: 99%
“…Variation in the ability of females to reject males of different sizes results in sexual selection for large male size (Crean and Gilburn, 1998;Crean et al, 2000). Male mate choice also operates on the basis of female fecundity (Pitafi et al, 1990) and longevity (Dunn et al, 2001). LMSP has been previously reported in Coelopa frigida with P 2 values increasing with the time interval between matings (Butlin, 1983).…”
Section: Introductionmentioning
confidence: 95%
“…Copulations typically last between 1 and 2 min but occasionally continue for longer. Males were stopped from mating for longer than 5 min to limit any possibility that variation in fertilisation success might be associated with copulation duration, although previous studies have revealed no such correlation (Pitafi, 1991). The matings were carried out in 1.5 ml microcentrifuge tubes to reduce the ability of females to successfully reject males.…”
Section: Methodsmentioning
confidence: 99%